Implementation of the teacher's role in implementing the Kurikulum Merdeka in elementary school - Maisy Aprilia; Dea Mustika (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
One of the latest initiatives from the Kementerian Pendidikan, Kebudayaam, Riset, dan Dikti (Kemendikbudristek) is the Merdeka Curriculum to improve the quality of students who have competitiveness in facing future developments. To implement a Merdeka Curriculum, the role of teachers is very crucial. This research aims to determine the implementation of the teacher's role in implementing the Kurikulum Merdeka using descriptive qualitative methods. The research was conducted at SDIT Fadhilah Pekanbaru by collecting data through observation, interviews, and documentation. The results of this research indicate that the Kurikulum Merdeka has been implemented by teachers, who play a role in (1) planning a learning program, starting from creating an ATP and being able to formulate specific learning objectives according to student needs; (2) implementing the program that has been created, namely by using varied learning methods and media and involving students in active learning; and (3) carry out regular evaluations and reflections to assess learning outcomes. In this study, researchers found several difficulties faced by teachers in implementing the Kurikulum Merdeka, including difficulties in time management and limited facilities and infrastructure. However, as professional educators, teachers still try to optimize existing facilities to implement a Kurikulum Merdeka with innovative and flexible learning according to the needs and demands of the Industrial Revolution 4.0. AbstrakSalah satu inisiasi terbaru dari Kementerian Pendidikan, Kebudayaam, Riset, dan Dikti (Kemendikbudristek) adanya Kurikulum Merdeka untuk meningkatkan kualitas peserta didik yang memiliki daya saing dalam menghadapi perkembangan zaman di masa depan. Untuk menerapkan Kurikulum Merdeka, peran guru sangat krusial. Penelitian ini bertujuan untuk mengetahui implementasi peran guru dalam penerapan Kurikulum Merdeka Belajar, dengan metode kualitatif deskriptif. Penelitian dilakukan di SDIT Fadhilah Pekanbaru dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa Kurikulum Merdeka telah diimplementasikan oleh guru, yang berperan dalam; (1) merencanakan program belajar, mulai dari pembuatan ATP dan dapat merumuskan tujuan spesifik pembelajaran sesuai dengan kebutuhan siswa (2) melaksanakan program yang telah dibuat, yaitu dengan menggunakan metode dan media pembelajaran yang variatif dan melibatkan siswa untuk belajar aktif; dan (3) melakukan evaluasi dan refleksi secara berkala untuk menilai hasil pembelajaran. Dalam studi ini peneliti menemukan beberapa kesulitan yang dihadapi guru dalam implementasi kurikulum merdeka, di antaranya adalah kesulitan dalam manajemen waktu, serta sarana dan prasarana yang terbatas. Namun sebagai seorang pendidik profesional, guru tetap berusaha mengoptimalkan fasilitas yang ada untuk menerapakan kurikulum merdeka dengan pembelajaran inovatif dan fleksibel sesuai kebutuhan dan tuntutan revolusi industri 4.0.Kata Kunci: Kurikulum merdeka; peran guru; sekolah dasar